MONITORING DETAK JANTUNG DAN MENAMPILKAN SUHU TUBUH MENGGUNAKAN MLX90614 BERBASIS ANDROID - Sunardi; Daud Ghaffar Mudzakkir (CV. Multi Kreasi Media, 2023)
Paramedics use heart rate and body temperature as a role or measure in knowing a person's physical and mental health. Because if one of the heartbeats or body temperature is abnormal, then further treatment must be carried out so that nothing unwanted happens. Beat Per Minute (BPM) is a unit of heartbeat in an object, an adult's heart beats between 60 to 100 times per minute is said to be under normal circumstances. Measuring body temperature is also important to know the condition of the body, normal body temperature in humans ranges from 36.0-37.5℃. This heart rate and body temperature monitoring tool is controlled using ESP 32, MLX90614 as a body temperature meter, MAX30102 as a heart rate meter, OLED LCD as a medium to display measurement results. The Blynk IOT application on android and web is also used for media display of measurement results that can be read in the database. From the results of the average heart rate value on the tool, the result is 84.7 Beat Per Minute (BPM) while the oxymeter is 83.8 BPM (Beat Per Minute). For body temperature, the result is 34.91 ℃, while the thermometer is 35.1 ℃. So that the percentage of error on the tool is 1.08% for BPM and 0.55% for ℃.